Darsie Latimer’s “Little Solidity,” or the Case for Homosexuality in Scott’s Redgauntlet - Incorvati, Rick (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractBy the early 1820s Walter Scott had been sharply criticized for conjuring up conspicuously passive heroes for his tales, but that criticism did not prevent him from presenting his reading public with his most singularly submissive character, Darsie Latimer, in 1824’s Redgauntlet. In fact, Scott devotes considerable energy in the novel to the delineation of a particular breed of unmanliness, linking Darsie’s inertia with his unusually strong emotional attachment to a schoolmate, his peculiar fascination with strong men, and his marked awkwardness around eligible women his own age. I argue that the coalescing of such features in one character warrants consideration of Darsie as a type of homosexual—that is, a character marked not only by an orientation of desire toward one’s own sex but also by a litany of character traits (among them, in this case, self-doubt, self-consciousness, and irresolution) which were typically associated with this non-normative desire. After considering evidence from this novel as well as from diary entries that reveal Scott’s views on sodomy and on wayward passions, I re-examine the Foucaultian contention that the homosexual was a late-nineteenth-century invention which transformed the sodomite into a species. Scott’s Redgauntlet gives us reason to believe that the conception of such a species was in place by the late Romantic period and that it was possible to consider this character type as distinct from the sodomite insofar as the former designated a disposition rather than the implication of sexual indulgence.